Clinical use of a fixed-dose combination of telmisartan and indapamide in hypertension. Expert Council resolution - A. O. Konradi; F. T. Ageyev; A. S. Galyavich; Yu. A. Karpov; Zh. D. Kobalava; Yu. V. Kotovskaya; S. V. Nedogoda; A. O. Nedoshivin; O. N. Tkacheva (Российский кардиологический журнал)
The aim of the expert council "First star duo of telmisartan and indapamide in the Russian Federation", dedicated to the introduction of a new fixed-dose combination of telmisartan and indapamide (modified-release tablets) into clinical practice was to formulate an expert opinion on the potential use of novel fixed-dose combination of telmisartan and indapamide in the treatment of hypertensive patients.